PERSPEKTIF STANDAR KECANTIKAN TERHADAP EMOSI WANITA BERDASARKAN KIDUNG AGUNG 1:5-6 - Loiksoklay, Pulela Dewi; Pattinaja, Aska Aprilano; Siahaya, Nally Beatrikh Kartini (Jurnal Teologi RAI, 2024)
The unwritten standard of beauty for women is white and clean. As a result, women face more emotional distress to achieve ideal beauty, but this standard of beauty is challenged in Song of Songs 1:5-6, which calls black and beautiful. This study is motivated by the gap in researchers who provide an understanding of the opposition to emotional distress from the standard of beauty from the perspective of women who say I am black but beautiful. The method used in writing this journal is qualitative with a literal study approach. In this writing, the author attempts to see and provide an understanding of the existence of self-acceptance beyond beauty standards based on Song of Songs 1:5. Thus, this research found that a false perspective of beauty can affect women's emotional disorders if it is not accompanied by self-acceptance and self-love.